Molecular characterization and function analysis of grouper (Epinephelus coioides) Bruton's tyrosine kinase BTK. Issue 77 (June 2018) - Mo, Ze-Quan; Han, Qing; Zeng, Yu-Long; Wang, Jiu-Le; Li, Xue-Zhu; Li, Yan-Wei; Sun, Hong-Yan; Li, An-Xing; Luo, Xiao-Chun; Dan, Xue-Ming
Abstract: Bruton's tyrosine kinase (BTK) is a Tec-family tyrosine kinase and plays a crucial role in B cell antigen receptor (BCR) signal pathway. Mutations in humans and mice BTK gene results in X-linked agammaglobulinemia (XLA) and X-linked immunodeficiency (XLD), respectively. To study the function of BTK in teleost, we cloned a BTK gene from orange-spotted grouper. Homology analysis showed that the grouper BTK (EcBTK) had a high amino acid identity with other vertebrates (63%–92%) and shared the highest amino acid identity with ballan wrasse Labrus bergylta BTK. EcBTK comprises a Bruton's tyrosine kinase pleckstrin homology (PH) domain, a Tec homology (TH) domain, a Src homology 3 (SH3) domain, a Src homology 2 (SH2) domain and a Protein Kinases, catalytic (PKc) domain. Tissue distribution analysis showed that EcBTK was mainly expressed in immune organs. EcBTK was uniform distributed throughout the cytoplasm of transfected HEK293T cells and overexpression of EcBTK slightly down-regulates NF-κB activity. Ibrutinib treatment can reduce the phosphorylation level of grouper's BTK. In groupers infected with Cryptocaryon irritans, up-regulation of EcBTK were not seen in the early stage of infected skin and gill until days 14–21. The phosphorylation level of grouper BTK was significantly increased in infected skin and gill. Highlights: BTK cDNA sequences was firstly identified from grouper. EcBTK was significant up-regulation in C. irritans infected gill and skin. Ibrutinib treatment can reduce the phosphorylation level of grouper's BTK.